To what extent do young chinese elites comply with COVID-19 prevention and control measures? - Yuanyuan Huang; Hua Zhang; Zixuan Peng; Min Fang (BMC, 2023)
Abstract Background During the COVID-19 pandemic, it is vital for individuals to comply with the government's prevention and control measures. This study aims to explore determinants of college students' compliance behaviour during the COVID-19 pandemic. Methods This study conducted an online survey among 3,122 individuals aged 18 and above from March to November 2022 in China. Individuals' compliance behaviour was divided into protective behaviour (that includes wearing a mask, maintaining a physical distance, and getting vaccinated) and restrictive behaviour (that includes offering health codes and a nucleic acid test certificate). Individuals' compliance motivation was divided into calculated motivation (including the fear of being infected, the fear of being published, and previous experience of pandemic prevention) and normative motivation (including the sense of social responsibility and trust in government). We defined young people aged between 18 and 24 with a college degree as young elites, and constructed ordinary least squares linear regression to compare their compliance behaviour with young people without a college degree (young non-elites), and non-young people with a college degree (non-young elites). Results Almost three years after the outbreak of the pandemic, Chinese individuals retained a high degree of compliance with COVID-19 prevention and control policies, particularly with respect to the provision of health codes. Young elites were more compliant with getting vaccinated, wearing a mask, providing health codes and testing results than their counterparts. The sense of social responsibility and trust in government were the major drivers of young elites' compliance behaviour during the pandemic. Young elites who were male, had a rural "hukou", and were not a member of the China Communist Party were more compliant with COVID-19 prevention and control measures. Conclusion This study found that young elites in China had high policy compliance during the COVID-19 pandemic. These young elites' compliance behaviour was driven by their sense of social responsibility and trust in government rather than the fear of being infected and the fear of being punished as a result of violating the regulations. We suggest that in the context of managing health crises, in stead of introducing punitive measures to enforce citizens to comply with the management measures, promoting citizens' sense of social responsibility and building a trusting relationship with citizens contrite to the enhancement of citizens' policy compliance.